2018
DOI: 10.1016/j.jacep.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Pacing-Induced Cardiomyopathy Following Cardiac Resynchronization Therapy

Abstract: CRT is highly efficacious in reversing PICM, with 72% of severe PICM patients achieving LVEF >35% and most of the improvement occurring within 1 year. These data support initial upgrade to a CRT pacemaker with consideration of further upgrade to CRT defibrillator after 1 year if LVEF remains ≤35%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 16 publications
9
98
0
1
Order By: Relevance
“…15,16 Electrical pacing from the right heart compromises the mechanical ventricular efficiency and causes dyssynchrony. 17 In addition, another study reported that the use of CRT was found to be associated with a better LVEF and a smaller LV volume over a 1 year and long-term follow-up period. This is an important reason for the development of PICM after PPM implantation, although the QRS duration derived by electrical pacing does not necessarily reflect the degree of mechanical dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Electrical pacing from the right heart compromises the mechanical ventricular efficiency and causes dyssynchrony. 17 In addition, another study reported that the use of CRT was found to be associated with a better LVEF and a smaller LV volume over a 1 year and long-term follow-up period. This is an important reason for the development of PICM after PPM implantation, although the QRS duration derived by electrical pacing does not necessarily reflect the degree of mechanical dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
“…* P < 0.05 compared to basal value within treatment groups (paired t test). [Colour figure can be viewed at wileyonlinelibrary.com] ventricles are paced in synchrony, aims to better emulate a physiological cardiac contraction and has demonstrated success in reversing the single-chamber pacing-induced cardiomyopathy (Eldadah et al 2006;Leclercq et al 2007;Bellmann et al 2016;Khurshid et al 2018). Interestingly, it has been observed in a clinical setting, that the functional improvements driven by CRT are more pronounced in individuals starting with asynchronous heart failure (Kirk & Kass, 2013), suggesting the restoration of synchrony has stronger biological effects than continuation of synchrony in heart failure.…”
Section: Clinical Relevancementioning
confidence: 99%
“…48,49 Despite the paucity of large randomized trials there is consensus that upgrading from ventricular pacing to CRT in PICM is beneficial and this is reflected in current guidelines. 44,50 However, the largest randomized trial comparing CRT to RV pacing (the Biopace study), enrolling 1810 patients, showed no significant differences in clinical outcomes, in terms of mortality and heart failure hospitalization. 51…”
Section: Cardiac Resynchronization Therapy (Crt)/biventricular Pacingmentioning
confidence: 99%